2005
DOI: 10.1073/pnas.0504921102
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression profiling of human blood reveals biomarkers for Huntington's disease

Abstract: We identified 322 mRNAs that showed significantly altered expression in HD blood samples, compared with controls (P < 0.0005), on two different microarray platforms. A subset of up-regulated mRNAs selected from this group was able to distinguish controls, presymptomatic individuals carrying the HD mutation, and symptomatic HD patients. In addition, early presymptomatic subjects showed gene expression profiles similar to those of controls, whereas late presymptomatic subjects showed altered expression that rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
293
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(316 citation statements)
references
References 19 publications
11
293
3
2
Order By: Relevance
“…Additionally, glucocorticoids have effects on peripheral blood cells and the hypothalamus-pituitary adrenal (HPA) axis, which is perturbed during depressive episodes of many patients (Gladkevich et al, 2004). Transcriptional profiling in whole blood has been used in the search for biomarkers for patients with neurological and other psychiatric disorders including patients with Parkinson's (Scherzer et al, 2007) and Huntington's disease (Borovecki et al, 2005), post-traumatic stress disorder Segman et al, 2005;Yehuda et al, 2009), schizophrenia (Kurian et al, 2011), bipolar disorder (Le-Niculescu et al, 2009;Padmos et al, 2008) and major depression (Segman et al, 2010;Spijker et al, 2010). Most of these studies have analyzed baseline gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, glucocorticoids have effects on peripheral blood cells and the hypothalamus-pituitary adrenal (HPA) axis, which is perturbed during depressive episodes of many patients (Gladkevich et al, 2004). Transcriptional profiling in whole blood has been used in the search for biomarkers for patients with neurological and other psychiatric disorders including patients with Parkinson's (Scherzer et al, 2007) and Huntington's disease (Borovecki et al, 2005), post-traumatic stress disorder Segman et al, 2005;Yehuda et al, 2009), schizophrenia (Kurian et al, 2011), bipolar disorder (Le-Niculescu et al, 2009;Padmos et al, 2008) and major depression (Segman et al, 2010;Spijker et al, 2010). Most of these studies have analyzed baseline gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…12 It has been reported that ATRX expression levels are elevated in the white blood cells of presymptomatic (1.6-fold) and symptomatic HD (2-fold) patients compared with the controls. 24 Given that deregulation of nucleosomal dynamics contributes to the HD pathogenesis and that ATRX expression is elevated in the peripheral blood of HD, it is reasonable to suggest that ATRX could have a role in chromatin remodeling and neurodegeneration in HD. Indeed, we found that ATRX is transcriptionally induced by mtHtt through activation of Cdx2.…”
Section: Discussionmentioning
confidence: 99%
“…All existing information, however, suggests that most of these individuals experience a period of apparent clinical and biological normalcy before entering a prodromal period in which there is active underlying disease without any evident clinical or functional consequences. Current evidence indicates that the causative processes involved in HD are present for at least 10 to 20 years before HD can be diagnosed clinically [21][22][23][24][25][26][27][28] on the basis of the unequivocal presence of the movement disorder.…”
Section: Neuroprotection In Premanifest Hdmentioning
confidence: 99%
“…21,28,30 Subtle cognitive, motor, psychiatric, [31][32][33] and metabolic abnormalities 34,35 are detectable in premanifest HD, and biochemical alterations are beginning to be detected in blood. 24,36 It is unknown whether the HD prodrome represents a stable condition until some decompensation causes manifest HD to emerge, or whether it is a continuum in which clinically silent neurodegeneration gradually accumulates sufficiently to cause unequivocal symptoms. The pace of the disease process can certainly vary over time, or can be accelerated by other stresses.…”
Section: Neuroprotection In Premanifest Hdmentioning
confidence: 99%